(untitled) (International Journal of Built Environment and Sustainability, 2017)
Accomplishment of green building design requirements and the achievement of the targeted credit points under a specific green rating system are known to be a task that is very challenging. Building Information Modeling (BIM) design process and tools have already made considerable advancements in green building design and performance analysis. However, Green building design process is still lack of tools and workflows that can provide real-time feedback of building sustainability and rating during the design stage. In this paper, a new workflow of green building design assessment and rating is proposed based on the integration of Visual Programing Language (VPL) and BIM. Thus, the aim of this study is to develop a BIM-VPL based tool for building envelope design and assessment support. The focus performance metric in this research is building Envelope Thermal Transfer Value (ETTV) which is an Energy Efficiency (EE) prerequisite requirement (up to 15 credits) in both Green Mark and GreenRE rating systems. The development of the tool begins first by creating a generic integration framework between BIM-VPL functionalities and ETTV requirements. Then, data is extracted from the BIM 3D model and managed using Revit, Excel and Dynamo for visual scripting. A sample project consisting of a hypothetical residential building is run and its envelope ETTV performance and rating score are obtained for the validation of the tool. This tool will support project team in building envelope design and assessment by allowing them to select the most appropriate façade configuration according to its performance efficiency and the green rating. Furthermore, this tool serves as proof of concept that building sustainability rating and compliance checking can be automatically processed through customized workflows developed based on BIM and VPL technologies.